A proopiomelanocortin‐derived peptide sequence enhances plasma stability of peptide drugs. Issue 17 (27th June 2020) - Löw, Karin; Roulin, Alexandre; Kunz, Stefan
Abstract : Bioactive peptide drugs hold promise for therapeutic application due to their high potency and selectivity but display short plasma half‐life. Examination of selected naturally occurring peptide hormones derived from proteolytic cleavage of the proopiomelanocortin (POMC) precursor lead to the identification of significant plasma‐stabilizing properties of a 12‐amino acid serine‐rich orphan sequence NSSSSGSSGAGQ in human γ3‐melanocyte‐stimulating hormone (MSH) that is homologous to previously discovered NSn GGH ( n  = 4–24) sequences in owls. Notably, transfer of this sequence to des‐acetyl‐α‐MSH and the therapeutically relevant peptide hormones neurotensin and glucagon‐like peptide‐1 likewise enhance their plasma stability without affecting receptor signaling. The stabilizing effect of the sequence module is independent of plasma components, suggesting a direct effect in cis . This natural sequence module may provide a possible strategy to enhance plasma stability, complementing existing methods of chemical modification. Abstract :